Association of the Platelet Glycoprotein IIIa PIA1/A2 Gene Polymorphism to Coronary Artery Disease but not to Nonfatal Myocardial Infarction in Low Risk Patients - Gardemann, Andreas; Humme, Jörg; Stricker, Jürgen; Nguyen, Quoc D.; Katz, Norbert; Philipp, Monika; Tillmanns, Harald; Hehrlein, Friedrich Wilhelm; Rau, Matthias; Haberbosch, Werner (Thrombosis and Haemostasis, 1998)
Background. The platelet membrane glycoprotein IIb/IIIa functions as a receptor for fibrinogen and von Willebrand factor during platelet aggregation. In a small case-control study, evidence has been presented that the PlA2 allele of the platelet glycoprotein GPIIIa PlA1/A2 gene polymorphism might be an independent risk factor for acute myocardial infarction (MI). Methods and Results. We explored the association of the PlA1A2 to the severity of coronary artery disease (CAD), as assessed angiographically in 2252 male individuals, and to myocardial infarction (MI). The severity of coronary heart disease (CHD) was also estimated by calculating a CHD score according to Gensini. The PlA genotype was determined by allele specific restriction digestion. Relation of the PlA2 allele to CAD: In the total population, the frequency of the PlA2 allele was not associated to the presence or to the extent of CAD. Also the CHD scores of PlA1/PlA2 genotypes were essentially the same. However, after exclusion of individuals with high BMI (≥26.9 kg/m2) and/or low apoAI (<1.43 g/l) PlA2PlA2 carriers had clearly higher CHD scores than PlA1PlA1 genotypes; PlA1PlA2 heterozygotes had intermediate values (p <0.05). After division of the study population into one group of individuals without any angiographic signs of CAD (CHD score = 0) and into another group of patients with severe CAD (CHD score (≥120), a strong association of the PlA2 allele with severe CAD was also found in the same low risk groups; e.g. exclusion of persons with high BMI and low apoAI resulted in an Odds ratio of 5.37 (1.46-19.7) (p <0.02). Relation of the PlA2 allele to MI: No association was found between PlA1/PlA2 genotypes and risk of MI neither in the total population nor in low risk subgroups.Conclusions. Whereas no difference in the distribution of allele and genotype frequencies between controls and survivors of MI could be detected, the PlA2 allele is associated with CHD in low risk patients.